Differential quantities of immune checkpoint-expressing CD8 T cells in soft tissue sarcoma subtypes - Cornelis Verhoef; Reno Debets; Yarne Klaver; Stefan Sleijfer; Dirk Grünhagen; Rebecca Wijers; Maud Rijnders; Astrid Oostvogels; Marcel Smid; Cor Lamers (Journal for ImmunoTherapy of Cancer)
Introduction Local T-cell immunity is recognized for its contribution to the evolution and therapy response of various carcinomas. Here, we investigated characteristics of tumor-infiltrating lymphocytes (TILs), as well as T-cell evasive mechanisms in different soft tissue sarcoma (STS) subtypes.Methods Liposarcoma, gastrointestinal stromal tumor (GIST), leiomyosarcoma, myxofibrosarcoma and pleomorphic sarcomas were assessed for T-cell numbers and phenotypes using flow cytometry. Next-generation sequencing was used to analyze T-cell receptor repertoire, mutational load, immune cell frequencies, and expression of immune-related genes.Results GIST, myxofibrosarcoma and pleomorphic sarcoma showed high numbers of CD8+ TILs, with GIST having the lowest fraction of effector memory T cells. These TILs coexpress the immune checkpoints PD1, TIM3, and LAG3 in myxofibrosarcoma and pleomorphic sarcoma, yet TILs coexpressing these checkpoints were near negligible in GIST. Fractions of dominant T-cell clones among STS subtypes were lowest in GIST and liposarcoma, whereas mutational load was relatively low in all STS subtypes. Furthermore, myeloid-derived cells and expression of the costimulatory ligands CD86, ICOS-L and 41BB-L were lowest in GIST when compared with other STS subtypes.Conclusion STS subtypes differ with respect to number and phenotypical signs of antitumor responsiveness of CD8+ TILs. Notably, GIST, myxofibrosarcoma and pleomorphic sarcoma harbor high numbers of CD8+ T cells, yet in the GIST microenvironment, these T cells are less differentiated and non-exhausted, which is accompanied with a relatively low expression of costimulatory ligands.